ANALISIS KIMIA BEBERAPA KAYU KURANG DIKENAL DARI NUSA TENGGARA BARAT - Gustan Pari; Djeni Hendra (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper deals with chemical analysis of ten lesser known wood species from Nusa Tenggara Bara The analyisi comprises of determination of holocellulose, cellulose, lignin, pentosan, silica, ash, moisture contents and solubility in cold water, hot water, sodium hydroxide and alcohol benzene content.The result shows that holiocellulose content ranges from 53,5 - 68. 8 percent, cellulose from 43. 0 - 62. 3 percent. Low cellulose content was formed in Duabanga molucana. Lignin content varie from 20.2- 24.7 percent, pentomn con- tent from 8.0 15.4 percent. Lignin and pentosan content of all wood species examined were in moderate and low. Moisture content ranged from 10.7 - 25.3 percent, ash content from 0.2 - 2.1 percent, silica from Q. 1-1.0 percent.The solubility in cold water ranged from 3.0 - 10.2 percent, in hot water from 5.4 – 14.1 percent, in one percent of sodium hydroxide solution from 9. 7 - 35.0 percent and in alcohol benzene (1:2) from 1.5-7.0 percent. The extractive contents of Elaeocarpus sphserlcus,Eugenia lineata Palaquium javaneae and Duabanga molucana wood species are having low component cless.flcus microcarpus and Trema orientalia wood sapecia had moderate extractwe component class Ailanthus malabarica, Aathoaspelalus cadamba and eugenia polyantha wood species included in high extractiue component. class Based on chemical analysis especially the cellulose and pentosan content of the 10 lasser known wood species from Nusa Tenggara Barat are suitable as raw material for pulp and peper industry.